2011 3rd International Conference on Computer Research and Development 2011
DOI: 10.1109/iccrd.2011.5764032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis the performance of a LDPC coded FSO system with Q-ary pulse-position modulation

Abstract: Free-space optical communication is an attractive and cost-effective solution for high-rate image, voice, and data transmission. However, optical wave propagation through the air experiences fluctuation in amplitude and phase due to atmospheric turbulence. In this paper, an analytical approach is presented to evaluate the bit error rate performance of a free space optical link using LDPC coded Q-ary optical PPM through atmospheric turbulence channel. Performance results are evaluated for multiple-laser and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It was observed that the LDPC coded MIMO FSO system using M-PPM provides better performance over the uncoded system in case of a strong atmospheric turbulence and large background noise set to -170 dBJ. A coding gain of 10 -20 dB was observed over the uncoded system at BER = 10 −12 [321], [322]. A comparison of serial concatenated PPM is made with LDPC coded PPM which shows low latency and improved performance for LDPC coded PPM in space-based optical links [323].…”
Section: •-Ppm Dppm Dappm Dpim Dhpimαmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the LDPC coded MIMO FSO system using M-PPM provides better performance over the uncoded system in case of a strong atmospheric turbulence and large background noise set to -170 dBJ. A coding gain of 10 -20 dB was observed over the uncoded system at BER = 10 −12 [321], [322]. A comparison of serial concatenated PPM is made with LDPC coded PPM which shows low latency and improved performance for LDPC coded PPM in space-based optical links [323].…”
Section: •-Ppm Dppm Dappm Dpim Dhpimαmentioning
confidence: 99%
“…It was observed that LDPC coded MIMO FSO system using M-PPM provides better performance over uncoded system in case of strong atmospheric turbulence and large background noise set to -170 dBJ. A coding gain of 10-20 dB was observed over uncoded system at BER = 10 −12 [192], [193]. Also, bit interleaved coded modulation (BICM) scheme proposed by I.B Djordjevic [192] provide excellent coding gain when used with LDPC coded FSO system.…”
Section: Table VI Comparison Of Variants Of Ppm Modulation Schemementioning
confidence: 99%
“…3 FSO transmission provides high-speed connections for disaster recovery and temporal networks. However, for many scenarios such as real-time transmission and broadcasting, retransmission is either expensive or impossible to implement, so using forward error correction (FEC) is promising and has been widely studied [2][3] [4]. Recent reviews [5] and [6] give an overview of coding methods for optical transmission.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, adaptation methods and transmission protocols are being actively discussed [1113]. For many scenarios such as real‐time transmission and broadcasting, retransmission is either expensive or impossible to implement, so using forward error correction (FEC) is promising and has been widely studied [1416].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an optical concatenated coding scheme combined RS and STBC is proposed in [5]. The performance of LDPC [6.7] is better than RS, so a concatenated system based on LDPC code and STBC is proposed in [8,9]. This scheme achieves not only diversity gain but also coding gain, thus achieving a much better link performance.…”
Section: Introductionmentioning
confidence: 99%